CONSTITUTIONAL AND LEGAL ORGANIZATION OF EARLY ELECTIONS (American Journal of Research in Humanities and Social Sciences, 2024)
Election is one of the components of responsible citizenship and a clear indication of the people’s awareness and their eagerness to establish democratic institutions and just governance. Since the popular will is the most effective force today and a democratic system cannot be imagined without its presence, and whenever this will is violated, the political system loses its legitimacy. The right of individuals to participate in political life is considered one of the basic rights, and people always seek to exercise this right whenever they deem it necessary to do so. There are many necessities that push people to demand urgent or early elections to end tyrannical rule and impose their will, and crises appear in many countries. Divisions at the political level pose a threat to the social and economic situation or as a result of popular discontent, so the need arises to speed up the elections so that the people can have their say.